The Effects Of The Yenikoy Treaty On The Armenians And The Russian-Armenian Collaboration In World War I - Nejla; Günay (Gazi Akademik Bakış)
After the Ottoman Empire lost the first Balkan war, its situation changed drastically. All the weaknesses of the army and the administration came into notice. The issue of the Armenian reforms resulted in the interfering of the Great Powers in the empire’s internal affairs. With the Yenikoy treaty signed between Russia and the Ottoman Empire on February 9th, 1914, the reform demands of the Armenians were met. After that treaty, though, it had been observed that the Armenians started losing allegiance to the state and began arming themselves. Moreover, the Russian pressure on the Ottoman Empire also increased. After the bursting out of the World War I, Armenians thought that they could gain independence from the state with the help of Russia and the other Allied Powers. Therefore, Armenian National Delegacy started recruiting Armenian volunteers to fight in the Russian army. These volunteers were organized as separate units by the Russians. Their duties were to conduct intelligence duties for the Russians and opening the frontiers for the Russian army by performing guerilla wars. Armenians successfully conducted their duties, which resulted in the retreatment of the Turkish army from lots of places, even including Van. However, the Turkish army also put some effort in band activities. In this study, both the effects of Russia and the other Allied Powers on the Armenians and their standpoints towards the Ottoman Empire will be investigated.